Liver transplantation. A twenty-year anniversary worthy celebration - Silva Jr, Orlando de Castro e; Martinelli, Ana de Lourdes Candolo (Medicina (Ribeirao Preto), 2021)
In the middle of the Covid-19 pandemic, we celebrate the 20th anniversary of the creation of the Institutional Program of Liver Transplantation, with emphasis on the first transplant performed during the first year of this century. We OCSJr and ALCM are currently retired, but we are obviously attached in an affective manner both to their colleagues and to the FMRP-USP institution. We believe that there are plenty of reasons to celebrate this anniversary.